Chemical composition modulates the adverse effects of particles on the mucociliary epithelium (Clinics, 2015)
OBJECTIVE:We compared the adverse effects of two types of real ambient particles; i.e., total suspended particles from an electrostatic precipitator of a steel mill and fine air particles from an urban ambient particulate matter of 2.5 µm, on mucociliary clearance.METHOD:Mucociliary function was quantified by mucociliary transport, ciliary beating frequency and the amount of acid and neutral mucous in epithelial cells through morphometry of frog palate preparations. The palates were immersed in one of the following solutions: total suspended particles (0.1 mg/mL), particulate matter 2.5 µm 0.1 mg/mL (PM0.1) or 3.0 mg/mL (PM3.0) and amphibian Ringer’s solution (control). Particle chemical compositions were determined by X-ray fluorescence and gas chromatography/mass spectrometry.RESULTS:Exposure to total suspended particles and PM3.0 decreased mucociliary transport. Ciliary beating frequency was diminished by total suspended particles at all times during exposure, while particulate matter of 2.5 µm did not elicit changes. Particulate matter of 2.5 µm reduced epithelial mucous and epithelium thickness, while total suspended particles behaved similarly to the control group. Total suspended particles exhibited a predominance of Fe and no organic compounds, while the particulate matter 2.5 µm contained predominant amounts of S, Fe, Si and, to a lesser extent, Cu, Ni, V, Zn and organic compounds.CONCLUSION:Our results showed that different compositions of particles induced different airway epithelial responses, emphasizing that knowledge of their individual characteristics may help to establish policies aimed at controlling air pollution.